Yoga Practice Is Beneficial for Maintaining Healthy Lifestyle and Endurance Under Restrictions and Stress Imposed by Lockdown During COVID-19 Pandemic - Nagarathna, Raghuram; Anand, Akshay; Rain, Manjari; Srivastava, Vinod; Sivapuram, Madhava Sai; Kulkarni, Ravi; Ilavarasu, Judu; Sharma, Manjunath N. K.; Singh, Amit; Nagendra, Hongasandra Ramarao (Frontiers in Psychiatry, 2021)
Uncertainty about Coronavirus disease 2019 (COVID-19) and resulting lockdown caused widespread panic, stress, and anxiety. Yoga is a known practice that reduces stress and anxiety and may enhance immunity. This study aimed to (1) investigate that including Yoga in daily routine is beneficial for physical and mental health, and (2) to evaluate lifestyle of Yoga practitioners that may be instrumental in coping with stress associated with lockdown. This is a pan-India cross-sectional survey study, which was conducted during the lockdown. A self-rated scale, COVID Health Assessment Scale (CHAS), was designed by 11 experts in 3 Delphi rounds (Content valid ratio = 0.85) to evaluate the physical health, mental health, lifestyle, and coping skills of the individuals. The survey was made available digitally using Google forms and collected 23,760 CHAS responses. There were 23,290 valid responses (98%). After the study's inclusion and exclusion criteria of yogic practices, the respondents were categorized into the Yoga (n = 9,840) and Non-Yoga (n = 3,377) groups, who actively practiced Yoga during the lockdown in India. The statistical analyses were performed running logistic and multinomial regression and calculating odds ratio estimation using R software version 4.0.0. The non-Yoga group was more likely to use substances and unhealthy food and less likely to have good quality sleep. Yoga practitioners reported good physical ability and endurance. Yoga group also showed less anxiety, stress, fear, and having better coping strategies than the non-Yoga group. The Yoga group displayed striking and superior ability to cope with stress and anxiety associated with lockdown and COVID-19. In the Yoga group, participants performing meditation reportedly had relatively better mental health. Yoga may lead to risk reduction of COVID-19 by decreasing stress and improving immunity if specific yoga protocols are implemented through a global public health initiative.